MITIGASI RESIKO USAHA PAKAIAN BEKAS - Rini, Puspa; Siregar, B. Wisman S.; Yulianto, Kampono I.; Freddy, John (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2022)
Business and selling are alternative solutions for alumni of the Tahfidz Islamic Boarding School, one of which is a recycled clothing fashion brand which can be done without a long process. In addition to the variations of the models that are very diverse and in accordance with the desires of young people's self-confidence, used clothes are relatively affordable. In fact, due to its "affordability", many teenagers are interested in not only using it as buyers but sellers. Problems then arise, including aspects of legality, halalness, hygiene, mitigating the risk of purchasing in a closed bale system. The purpose of this service is to provide counseling on mitigating the risks of trying used clothes if the scale of purchase (for resellers) is in the "wholesale/bal" system (closed packaging whose condition cannot be checked first). With this counseling, sellers can have comprehensive insight into risk mitigation: selling risk mitigation, mitigating the risk of justification for society, halal-haram, legal/illegal, to the most important being able to accurately calculate forecasts for wholesale purchases or the contents of 'bals' very tightly closed. This is a business mitigation, if the calculation is wrong, it will certainly have a fatal impact, namely no return of capital, aka loss. The solution delivery technique is counseling. Counseling is intended to broaden the horizons of students in anticipating all the risks of trying used clothes. The result of the service activity is that the high risk mitigation of used clothes is the amount of damaged goods which is very high risk according to the term buying cats in sacks. For students who are going to buy retail or items that are already on display, it is more recommended because they can be checked before buying. As for purchases by wholesale in closed bales, including subhat (very doubtful), this has invited a lot of debate, but the servant's recommendation is to buy by "head quantity", ie opening one bale with certainty of buying 10 to 25 units of goods.